Accelerating the development of artificial biocrusts using covers for restoration of degraded land in dryland ecosystems. (20th August 2020) - Zhao, Yang; Wang, Nan; Zhang, Zhishan; Pan, Yanxia; Jia, Rongliang
Abstract: Recent research has revealed the potential for using cyanobacteria inoculation to promote biocrusts on sandy drylands. There is global interest in using this approach to combat land degradation. Nevertheless, in order to use this biotechnology on a large scale, researchers must explore technologies that are simple and efficient to implement. To achieve this aim, we tested the effects of different covers to control dust and stabilize sand surfaces measures—that is, nonwoven fabric, dust‐proof net, and sun‐shading net—on colonization and development of artificial cyanobacteria crusts on the southeast edge of the Tengger Desert in Northern China. After 80 days, cyanobacteria crusts occurred in all inoculated soils. The best results occurred when using fresh cyanobacteria were covered with two‐layer nonwoven fabric and one‐layer sun‐shading net; this treatment resulted in 50.0% biocrust cover, 2.88 mm biocrust thickness, 19.21 μg cm 2 chlorophyll a concentration, 79.05 μg cm 2 total carbohydrate content, and 10.00 m s −1 threshold friction velocity, which is significantly higher than sand (3.70 m s −1 ). The results suggest that covering with nets can accelerate development of artificial cyanobacteria crusts, because covers improve micro‐environments and remove barriers limiting biocrust colonization. This study describes a potential approach to reconstruct or recover biocrusts, and to restore degraded land in dryland ecosystems.